The concept of contractual justice - Ternera Barrios, Francisco (2007)
Mainly the legislator and the judge have consulted the concept of contractual justice. In the first case, one is the implementation of generalremedies. In the second, we recognize particular solutions. In this article named Contractual justice: in search of the lost conceptinstitutions appear that inform the important place to us that in our days occupies the concept of contractual justice, formerly lost